The Role of Japan in the Intraregional Trade of the Far East - Koo, Anthony Y. C.; Liang, C. C. (The Review of Economics and Statistics, 1953)
IN the Far East, the overall volume of intraregional trade is not as substantial as that of Europe, but much larger than that of Latin America.2 One rather unique and very interesting feature of Far Eastern intraregional trade is that one country, namely, Japan, stands out prominently, from the point of view of both the character and magnitude of its trade. Japan contributed about one-third of the Far Eastern intraregional trade in the immediate prewar years (32.3 per cent for 1935, 34.5 per cent for 1937, and 38.o per cent for I938). Immediately after the cessation of hostilities, its share suffered a sharp reduction, but again became a significant percentage of the total in 1949 (I6.5 per cent). The ratio of Far Eastern intraregional trade to its total export, and Japan's share in intraregional trade showed a tendency to fluctuate together.3 Since Japan's share was about one-third in the prewar period and its intraregional imports were related to the volume of total intraregional exports, several questions may be raised with regard to the future role of Japan in the intraregional trade of the Far East. What are the initial and secondary effects of Japan's imports from the Far East on the intraregional exports of the countries of this region? Does such relationship in the prewar period remain true in the postwar period? If there is a change of preand postwar relationships, what are some of the reasons for the change? How are Japan's imports from the Far East related to the over-all exports of the region to all countries? This paper is a preliminary attempt at an analysis of the above questions.